A Further Look at Therapeutic Interventions for Suicide Attempts and Self-Harm in Adolescents: An Updated Systematic Review of Randomized Controlled Trials - Iyengar, Udita; Snowden, Natasha; Asarnow, Joan R.; Moran, Paul; Tranah, Troy; Ougrin, Dennis (Frontiers in Psychiatry, 2018)
Background: Suicide attempts (SA) and other types of self-harm (SH) are strong predictors of death by suicide in adolescents, emphasising the need to investigate therapeutic interventions in reduction of these and other symptoms. We conducted an updated systematic review of randomised controlled trials (RCTs) from our previous study reporting therapeutic interventions that were effective in reducing SH including SA, while additionally exploring reduction of suicidal ideation (SI) and depressive symptoms (DS). Method: A systematic literature search was conducted across OVID Medline, psycINFO, PubMed, EMBASE, and Cochrane Library from the first available article to October 22nd, 2017, with a primary focus on RCTS evaluating therapeutic interventions in the reduction of self-harm. Search terms included self-injurious behaviour; self-mutilation; suicide, attempted; suicide; drug overdose. Results: Our search identified 1,348 articles, of which 743 eligible for review, yielding a total of 21 studies which met predetermined inclusion criteria. Eighteen unique therapeutic interventions were identified among all studies, stratified by individual-driven, socially driven, and mixed interventions, of which 5 studies found a significant effect for primary outcomes of self-harm and suicide attempts (31.3%), and 5 studies found a significant effect for secondary outcomes of suicidal ideation and depressive symptoms (29.4%) for therapeutic intervention vs. treatment as usual. Collapsing across different variations of Cognitive Behaviour Therapy (CBT), and classifying Dialectical Behaviour Therapy for Adolescents (DBT-A) as a CBT, CBT is the only intervention with replicated positive impact on reducing self-harm in adolescents. Conclusion: While the majority of studies were not able to determine efficacy of therapeutic interventions for both primary and secondary outcomes, our systematic review suggests that individual self-driven and socially-driven processes appeared to show the greatest promise for reducing suicide attempts, with benefits of combined self-driven and systems-driven approaches for reducing overall self-harm. Further RCTs of all intervention categories are needed to address the clinical and etiological heterogeneity of suicidal behaviour in adolescents, specifically suicidal ideation and depressive symptoms.